Asymmetric Synthesis and Antimicrobial Activity of Some New Mono and Bicyclic Î²-Lactams - A. Taslimi; M. Shekarriz; A. A. Jarrahpour (Molecules, 2004)
Reaction of the amino acid D-phenylalanine ethyl ester (4) with cinnamaldehyde gave chiral Schiff base 5, which underwent an asymmetric Staudinger [2+2] cycloaddition reaction with phthalimidoacetyl chloride to give the monocyclic Î²-lactam 6 as a single stereoisomer. Ozonolysis of 6 followed by reduction with lithium aluminum tri(tert-butoxy) hydride afforded the hydroxymethyl Î²-lactam 8. Treatment of 8 with methansulfonyl chloride gave the mesylated monocyclic Î²-lactam 9, which was converted to the bicyclic Î²-lactam 10 upon treatment with 1,8-diazabicyclo[5,4.0] undec- 7-ene (DBU). Deprotection of the phthalimido group in Î²-lactams 6 and 10 by methylhydrazine and subsequent acylation of the free amino Î²-lactams with different acyl chlorides in the presence of pyridine afforded mono and bicyclic Î²-lactams 14a-d and 15a-d respectively. The compounds prepared were tested against Escherichia coli, Staphilococcus citrus, Klebsiella pneumanie and Bacillus subtillis. Some of these compounds showed potential antimicrobial activities.